Current Trends in Improving of Artificial Joints Design and Technologies for Their Arthroplasty - Poliakov, Aleksandr; Pakhaliuk, Vladimir; Popov, Valentin L. (Frontiers in Mechanical Engineering, 2020)
There is a global tendency to rejuvenate joint diseases, and serious diseases such as arthrosis and arthritis develop in 90% of people over 55 years of age. They are accompanied by degradation of cartilage, joint deformities and persistent pain, which leads to limited mobility and a significant deterioration in the quality of life of patients. For the treatment of these diseases in the late stages, depending on the indications, various methods are used, the most radical of which are methods of joint arthroplasty and, in particular, total arthroplasty. Currently, total arthroplasty is one of the most effective and high-quality surgical operations at the relevant medical indications. However, complications may also arise after it, leading, inter alia, to the need for repeated surgical intervention. In order to minimize the likelihood of complications, the artificial joints used in total arthroplasty and the technology of their fabrication are constantly being improved, which leads to the emergence of new designs and methods for their integration with living tissues. At the same time, at the moment, the improvement of traditional designs and production technologies has almost reached the top of their art, and their further improvements can be insignificantly or are associated with the use of the most up-to-day technologies, allowing for friction couples with low tribological properties to provide for them high ones, for example, gradient increase hardness in the couple titanium alloy on titanium alloy. This paper presents the current state of traditional technical means and technologies for joint arthroplasty. The main attention is paid to the analysis of the latest technologies in the field of joint arthroplasty, such as osseointegration of artificial joints, the improvement of materials with the property of osteoimmunomodulation, the improvement of joint arthroplasty technologies based on the modeling of dynamic osteosynthesis, as well as the identification of possible unconventional designs of artificial joints that contribute to these technologies, predictive assessment of areas for technologies improvement.